Representations of women in selected works of Herbert George De Lisser (1878-1944) - Urbanowicz, Donna-Marie (2013)
This thesis examines the intellectual significance of early Caribbean writer Herbert George de Lisser in his literary writings and as such is a work of recovery and criticism. Each chapter concentrates on a specific, predominantly European, literary genre and investigates how de Lisser experiments with these genres in order to not only support and recognise the emergence of a local national literature, but also to create a cultural national identity based upon the symbolic use of women to define Jamaica as a nation. Situating de Lisser within colonial discourse and the socio political arena of the British Empire, the introduction sets out the postcolonial theoretical framework and relocates de Lisser within the context of West Indian literature, debating his literary neglect alongside his need to be reclaimed. Chapter I debates the traditional notions of nationhood and examines the dislocation and (re)gendering of nation and nationhood through the lens of women as founders of a nation with the main emphasis on his novel "Anacanoa." Chapter II concentrates on de Lisser's "historical" novels and explores the representation of heroism and the search for a national identity in two of de Lisser's novels, Revenge and Psyche, written at the beginning and the end of his career. This chapter examines the way in which the novels' (re)negotiation of the representations of heroism is explored within individual characters. Chapter III examines women as a symbol of Jamaica through the lens of female independence and national identity. The focus of this chapter rests on de Lisser's literary works that have received a limited amount of literary investigation, namely Jane's Career and Susan Proudleigh, with a third novel "Myrtle and Money" which is not only a sequel to Jane's Career (although written some 30 years later), but also creates a trilogy of texts that serves to represent the political complexities of early twentieth century Jamaica. Chapters IV and V act as sister chapters and examine the representation of women through the (re)clamation and (re)creation of folk legends and the commodification of literature in the novels Morgan's Daughter and The White Witch of Rosehall. These chapters consider how de Lisser's appropriation of a legend encourages that legend to evolve into a symbol for nationalism and historical heritage. Experimenting with the genres of sentimental literature and gothic fiction respectively, de Lisser investigates the dichotomy of European and Jamaican cultures. Chapter VI focuses upon the general constructions of nationhood which are founded upon traditional hegemonic public and private spheres. With an in-depth investigation into his periodical Planters' Punch which was produced from 1920-1945, this chapter analyses how de Lisser continuously blurs these spherical boundaries by creating strong women who are capable of fulfilling the "role" of the male in civilised society and therefore relocates them into the public arena. Finally, the conclusion explores de Lisser's perception of women and highlights how by investigating his literary works through his representation of women, de Lisser is able to be reconciled within a more delineated and inclusive Caribbean literary canon.